(3ZQQ GdHdGZIs - (3gdGd GdUCHjA , gdGd Hf GdeMSf Hf EHQGgje Hf gdGd GdMQGfj, CHh GdMSjf , CHh GdMSf,J (B448 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdChd HdG GHJOGA hGdBNQ HdG GfJgGA s
(3fSNI QGHYI s
(3PcQ ajg Cfg GbJVH aUhdkG LGeYI dBcKQ eG jcJH Yf GdSdWGf hJJQOO Hjf GdENhGf hJJYGhO ai GdecGJHGJ hGdeNGWHGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B92 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B151s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B503 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs